KNOWLEDGE INTEGRITY IN METHODOLOGY OF INTELLECTUAL SCIENTIFIC-RESEARCH SYSTEMS - V. M. Koleshko; A. V. Gulay; V. A. Gulay (Наука и техника)
The paper analyzes a category of knowledge integrity in philosophical and methodological conception of the intellectual technology. Relationship of knowledge integrity and its uncertainty in the methodology of intellectual scientific research is considered in the paper. The paper  reveals a role of purpose uncertainty of intellectual research process in formation of knowledge integrity properties. An analysis of integrity notion functioning has been executed while considering a problem on relationship of general and partial components. The paper shows changes in the given relationship while making transition from value-orientated research process to purpose-orientated scientific investigation. Determination of diffusion, differentiated and integrated knowledge integrity is shown at various stages of intellectual scientific research.